The Generative Mechanism of Boomerang Intention: From the Perspective of Legacy Identification - Tian, Zehui; Yuan, Qinghong; Qian, Shanshan; Liu, Yanyan (Frontiers in Psychology, 2022)
Boomerang employment has become an increasingly important third way to obtain employees, yet little research has focused on how do ex-employees want to come back. Drawing from social identity theory, we propose that legacy identification could increase boomerang intention and that both perceived corporate prestige and psychological contract violation could increase boomerang intention through legacy identification. The cooperative relationship between the former organization and the current organization could enhance these effects. Results from a two-time points survey of 202 Chinese employees showed that legacy identification is positively correlated with boomerang intention, and that perceived corporate prestige is positively correlated with boomerang intention via legacy identification, psychological contract violation is negatively correlated with boomerang intention via legacy identification. Besides, the positive effect of legacy identification on boomerang intention, the positive indirect effect of corporate prestige on boomerang intention via legacy identification, and the negative indirect effect of psychological contract violation on boomerang intention via legacy identification are all stronger when there is a cooperative relationship. Theoretical and practical implications are discussed.